Deposit-Lending Synergies: Evidence from Chinese Students at U.S. Universities - Yang, Jun (Journal of Financial and Quantitative Analysis, 2022)
Abstract This paper exploits an influx of Chinese students to U.S. universities from 2000 through 2018 to study synergies between banks’ deposit-taking and lending activities. Banks that are more recognizable by Chinese students experience higher deposit inflows and increase their local credit supply. This credit supply expansion only occurs in information-sensitive credit markets: small business loans and second lien mortgages. Such increase concentrates in nontradable sectors and is more pronounced at locations where managers have more autonomy. The results indicate that deposits from local consumers convey private information about the local credit market, which helps banks in information-sensitive lending.